Pemberdayaan Masyarakat Dalamm Pencegahan Dan Penanganan Preeklamsia Pada Ibu Hamil - Delladari Mayefis; Jessica Tiranda; Apriyani; Emilda Adhami; Feby Valentine (Jurnal Pengabdian Masyarakat Akademisi, 2022)
Preeclampsia is hypertension that occurs after 20 weeks of gestation accompanied by proteinuria. Preeclampsia itself is a risk factor for complications in mother and baby. Complications are eclampsia, pulmonary edema, placental abruption, oligohydramnios and can cause maternal death. Long-term impacts can also occur in babies born to mothers with preeclampsia, such as low birth weight due to premature labor or experiencing stunted fetal growth, fetal distress, and contributing to the large number of perinatal morbidity and mortality (Widya, 2016).